(untitled) (Journal of Philosophy Culture and Political Science, 2026)
Modern scientific discoveries across various fields contribute to the development of new principles for studying human beings and consciousness. Although numerous theories of mind exist, the question of how consciousness differs depending on geographical and cultural context remains insufficiently explored. The purpose of this article is to provide a comparative analysis of the philosophy of consciousness within Western and Eastern philosophical traditions. The study applies general scientific and specific methods, including analysis, synthesis, induction, generalization, comparative, and content analysis. To explain the phenomenon of consciousness, the works of prominent representatives of Western and Eastern philosophy were examined. Within Islamic philosophy, the features of Islamic monotheism and the relationship between thought and the body are discussed. Western philosophy of consciousness is analyzed through D. Hofstadter’s concept of the essence and “self-model” of consciousness and D. Chalmers’ theory of the elements of consciousness. The research identifies fundamental similarities and differences in the interpretation of consciousness in Western and Eastern traditions and provides an analytical evaluation. The practical significance lies in comparing the value foundations of societies through the application of comparative analysis in the study of the philosophy of consciousness. Keywords: comparative studies, elements of consciousness, thought experiments, relationship between mind and matter, Islamic consciousness, artificial intelligence.